PENINGKATAN KUALITAS WARNA RAMBAK CAKAR MELALUI SOSIALISASI PENAMBAHAN BAHAN TAMBAHAN PANGAN (BTP) - Irvia Resti Puyanda; Rynati Dwi Cahyaningrum; Akhmad Mustofa (LPPM Universitas Bina Bangsa, 2023)
Color is one of the parameters in seletecting rambak products. When displaying in market, rambak cakar products are often found with heterogeny colors. One of the Home Industries (IRT) of rambak in Klaten city experienced a heterogen color problem which resulted in fluctuations in product sales. This community service program aims to provide information and training on the addition of lime paste as food addictive to improve the color quality of rambak cakar. The methods used in this service include; 1) Socialization, 2) Training, 3) Evaluation. From the socialization, it was found that the owners and employees in the production division understood howto use and apply lime paste as food addictive. The training (practice) stated that the addiotion of 2% lime paste had an effect on the rambak cakar’s brightness. At the evaluation stage, it was seen that the value of the paired comparison test on 20 panelists regarding the color characteristics of rambak cakar was 19 at the t level 1%, which indicated that the color produced were different